2020
DOI: 10.3917/reco.pr2.0156
|View full text |Cite
|
Sign up to set email alerts
|

Les déterminants locaux de la participation numérique au grand débat national : une analyse économétrique

Abstract: Les auteurs remercient les journalistes du Parisien et les concepteurs de l'application Entendre la France pour le partage de leurs données sur la mobilisation et le soutien aux Gilets jaunes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Although the movement has received attention in the news and social media, a theoretical analysis of the factors explaining the emergence and continued persistence of the movement is only slowly emerging. Nevertheless, despite a scarcity of empirical research (for exceptions, see Bennani, Gandré & Monnery, 2019;Boyer at al., 2019), it is clear that the Yellow Vest movement deserves attention from social scientists. As an initially spontaneous and grassroots rural uprising without apparent organizational structures or leaders, the Yellow Vests has led to substantial policy change and concessions on the part of the French government, changing the political landscape in France.…”
mentioning
confidence: 99%
“…Although the movement has received attention in the news and social media, a theoretical analysis of the factors explaining the emergence and continued persistence of the movement is only slowly emerging. Nevertheless, despite a scarcity of empirical research (for exceptions, see Bennani, Gandré & Monnery, 2019;Boyer at al., 2019), it is clear that the Yellow Vest movement deserves attention from social scientists. As an initially spontaneous and grassroots rural uprising without apparent organizational structures or leaders, the Yellow Vests has led to substantial policy change and concessions on the part of the French government, changing the political landscape in France.…”
mentioning
confidence: 99%
“…The proposals were incorporated into law later that month. At the same time, the president also declared a "Great National Debate" (Bennani et al, 2019) with terms set by the executive, focusing on "taxation and public spending, the organization of the state and public services, the ecological transition, democracy and citizenship", and was to last two months. The organization of this great debate, a form of "procedural concession" (Lamy, 2019) partially achieved the government's strategic goal of taking over the modalities of discussion in the public sphere.…”
Section: State Response: Carrot and Stickmentioning
confidence: 99%
“…Second, in an openanswer field, survey participants had the opportunity to describe how the most important problem identified earlier should be mitigated (N = 123 626). Although the survey does not contain individuallevel data on socio-demographic or other variables, an analysis of the ZIP codes of survey participants has shown that some sub-groups, such as urban, welleducated, and older are likely to be over-represented (Bennani et al 2019, Fourniau 2019. This specific subset of French society is arguably politically influential.…”
Section: Leveraging the French Grand Débat National As Original Data ...mentioning
confidence: 99%